Isolating the benefits of fluid restriction in patients with heart failure: A pilot study. (December 2015) - Reilly, Carolyn Miller; Higgins, Melinda; Smith, Andrew; Culler, Steven D.; Dunbar, Sandra B.
Background: Fluid restriction (FR) in persons with heart failure (HF) is often prescribed, yet self-regulation and the troublesome symptom of thirst are difficult for patients to manage. Aims: The purpose of this pilot study was to test an educational and behavioral intervention (EBI) on adherence with prescribed FR and outcome measures of fluid congestion, symptom distress, and health related quality of life (HRQL). Secondary aims were to describe the relationships between self-reported and objectively measured determinants of fluid status and symptoms, and assess the psychometric properties of piloted instruments, and intervention effect sizes. Methods: NYHA Class II-IV ( n =25, 44-83 years, 56% male, 20% minority, mean EF 23.0+11.7%) participants were randomized to the EBI or attention control (AC) and evaluated at baseline, 3 and 6 months. Results: EBI patients trended toward decreasing fluid ingestion ( p =0.08), experienced less HF symptom frequency ( p =0.13) and severity ( p =0.06), and increased symptoms of thirst ( p <0.01) across time. Whereas HRQL remained stable in the EBI group, it improved in the AC group over time ( p =0.01). There were no significant differences in clinical measures of fluid congestion between groups. Conclusions: These outcomes suggest that patients receiving the EBI drank slightly less fluid, experienced less typical HF symptoms, greater thirst distress and stable HRQOL. Moderate to large effect sizes for the measures used were observed, and outcomes suggest that a randomized trial of various levels of FR would not potentiate fluid congestion but should specifically address preservation of HRQOL and thirst symptoms.